The Use of Korean Language Reflecting the Concepts of War Metaphors in Economic News - Thongtanangkula, Kannaphatt (Journal of Social Sciences Naresuan University, 2025)
This research studies the concept of war in Korean economic news. Data was collected from the Naver website, a popular search engine platform among Koreans, and data was analyzed from texts and language forms that are war metaphors used by Korean online media to report economic news based on cognitive linguistics theory and conceptual metaphor analysis. The results of the analysis of the metaphor “economy is war” reveals that the characteristics of language forms in Korean economic news reflected ten other concepts that are components of war, namely 1. economic era is era of war 2. economic goal is war target 3. scale of economic competition is scale of war 4. duration of economic competition is duration of war 5. economic allies and partners are allies and enemies in war 6. economic strategy is war tactics 7. economic conditions are war situations 8. economic tools are war weapons 9. economic competition grounds are war locations and 10. economic outcomes are outcomes of war. The analysis of conceptual metaphors found that the concept “economic policy is a war strategy” is the most used, followed by “economic tools are war weapons” and “economic goals are war goals”, respectively. These concepts reflect the Korean people’s idea of how to win a war, and the economy emphasizes effective tactical planning and strategy execution, and the selection of appropriate combat and defense methods for the situation. In addition, importance is given to the quality and readiness of weapons and equipment in order to achieve war and economic goals.